Phosphorus-doped nanocarbon cage material, lithium ion capacitor electrode material, lithium ion capacitor negative electrode and preparation method thereof
By doping phosphorus in the nanocarbon cage and building a hierarchical pore structure, the problems of low specific capacity and poor rate performance of the nanocarbon cage are solved, and the high specific capacity and good cycle stability of the negative electrode of the lithium-ion capacitor are achieved.
Patent Information
- Application Number
- CN202111256391.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-10-27
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2041-10-27
AI Technical Summary
As the negative electrode material of lithium-ion batteries, nano-carbon cages have problems such as lower specific capacity and poor rate performance, and cannot meet the requirements of higher energy and power density.
By using nickel salts, organic acids and phosphorus-containing compounds as raw materials, phosphorus-doped nanocarbon cage materials are prepared, and high-temperature calcination and pickling methods are used to achieve the incorporation of phosphorus atoms and the construction of hierarchical pore structures.
The obtained phosphorus-doped nanocarbon cage material has excellent specific capacity, cycling performance and rate performance. The single electrode specific capacity exceeds 400mAh/g, and the capacity retention rate exceeds 95% after 500 cycles.
Smart Images

Figure CN116031076B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of electrochemical energy storage, and in particular to a phosphorus-doped nano-carbon cage material, a lithium ion capacitor electrode material, a lithium ion capacitor negative electrode and a preparation method thereof. Background Art
[0002] As a new type of nanocarbon material, nanocarbon cages have a hollow structure and a high degree of graphitization. They show broad application prospects in many fields such as catalysis and energy storage, and have attracted the interest of a wide range of researchers.
[0003] At present, the preparation of nano carbon cages is mainly based on the template method. CN101284663A discloses a method for preparing a large number of high-quality hollow carbon nano cages, which uses magnesium oxide as a template and prepares nano carbon cages by a vapor deposition method. The nano carbon cage has a large specific surface area and exhibits very excellent capacitance performance as a supercapacitor electrode. Hu et al. ("Carbon Nanocages as Supercapacitor Electrode Materials." Adv. Mater. 2012, 24, 347-352) prepared nano carbon cages using the template method, and its specific capacitance reached 260F / g.
[0004] Another method for synthesizing nanocarbon cages is to pyrolyze transition metal salts. Xu et al. (ACS Nano. 2020, 14, 11, 16161) prepared nanocarbon cages by pyrolyzing nickel citrate hydrate, which not only have a high degree of graphitization, but also show a high specific capacity as a negative electrode for potassium ion batteries.
[0005] The unique hollow structure and excellent conductivity of nanocarbon cages make them more widely used in the field of energy storage devices, and they are gradually becoming one of the potential substitutes for graphite, the negative electrode material of lithium-ion batteries. However, nanocarbon cages also face the problems of low specific capacity and poor rate performance, and cannot meet the requirements of higher energy and power density of lithium-ion batteries. Therefore, the incorporation of heteroatoms and the construction of hierarchical pore structures are effective means to improve the performance of nanocarbon cages. For example, the incorporation of phosphorus atoms can increase the defects and carbon layer spacing in carbon materials, change the charge distribution, and improve the lithium storage performance of the material.
[0006] At present, about the preparation of phosphorus-doped nano carbon cage, Guo et al. (" Comprehensive electronic structure characterization of pristine and nitrogen / phosphorus doped carbon nanocages. "Carbon 103,2016,480-487) use triphenylphosphine as phosphorus source, utilize the method for vapor deposition to prepare phosphorus-doped nano carbon cage. However, this process is more complicated, and the preparation cost is high, which is not conducive to the batch production of phosphorus-doped nano carbon cage. In addition, the existing process has certain difficulty for realizing the incorporation of phosphorus atoms and the construction of hierarchical pore structure at the same time. Summary of the invention
[0007] The purpose of the present invention is to overcome the above problems existing in the prior art and provide a phosphorus-doped nanocarbon cage material, a lithium ion capacitor electrode material, a lithium ion capacitor negative electrode and a preparation method thereof. When the lithium ion capacitor negative electrode prepared by the phosphorus-doped nanocarbon cage material is used in a lithium ion capacitor, it exhibits excellent specific capacity, cycle performance and rate performance.
[0008] In order to achieve the above object, the present invention provides a phosphorus-doped nanocarbon cage material in a first aspect. The nanocarbon cage material has a microporous structure and a mesoporous structure. The total specific surface area of the nanocarbon cage material is 300-600 m 2 / g, the specific surface area of micropores is 50-130m 2 / g, accounting for 10-25% of the total specific surface area; the average pore size is 10-20nm; the atomic percentage content of carbon on the surface of the nano carbon cage material measured by X-ray photoelectron spectroscopy is 90-97.5%, and the atomic percentage content of phosphorus is 0.01-1%.
[0009] A second aspect of the present invention provides a method for preparing a phosphorus-doped nanocarbon cage material, the method comprising the following steps:
[0010] (1) providing a homogeneous solution containing a nickel salt, an organic acid, a phosphorus-containing compound and a solvent, and then removing the solvent from the homogeneous solution to obtain a precursor material;
[0011] (2) calcining the precursor material at high temperature under the protection of an inert atmosphere to obtain a primary product;
[0012] (3) contacting the primary product with an acid for reaction, and then performing solid-liquid separation.
[0013] The third aspect of the present invention provides a lithium ion capacitor electrode material, which contains an active substance, a conductive agent and a binder. The active substance is the phosphorus-doped nanocarbon cage material described in the first aspect or the phosphorus-doped nanocarbon cage material prepared according to the method described in the second aspect.
[0014] A fourth aspect of the present invention provides a negative electrode for a lithium ion capacitor, the negative electrode comprising a current collector and an electrode material coated and / or filled on the current collector, the electrode material being the lithium ion capacitor electrode material described in the third aspect.
[0015] The fifth aspect of the present invention provides a method for preparing a negative electrode of a lithium ion capacitor, the method comprising coating and / or filling a slurry containing an active material, a conductive agent, a binder and a solvent on a current collector, drying, and rolling or not rolling, wherein the active material is the phosphorus-doped nanocarbon cage material described in the first aspect or the phosphorus-doped nanocarbon cage material prepared according to the method described in the second aspect.
[0016] Through the above technical solution, the present invention has the following advantages:
[0017] (1) The phosphorus-doped nanocarbon cage material provided by the present invention has a microporous structure and a mesoporous structure, and its total specific surface area is 300-600m 2 / g, the specific surface area of micropores is 50-130m 2 / g, accounting for 10-25% of the total specific surface area; the average pore size is 10-20nm; the atomic percentage content of carbon on the surface of the nano carbon cage material measured by X-ray photoelectron spectroscopy is 90-97.5%, and the atomic percentage content of phosphorus is 0.01-1%. The phosphorus-doped nano carbon cage material provided by the present invention has a hierarchical pore structure with mesopores as the main and micropores as the auxiliary. The negative electrode of the lithium ion capacitor prepared by using the material shows very excellent specific capacity, cycle performance and rate performance. The single electrode specific capacity exceeds 400mAh / g, and the capacity retention rate after 500 cycles exceeds 95%.
[0018] (2) The method provided by the present invention uses nickel salt, organic acid and phosphorus-containing compound as raw materials to prepare precursor materials, and combines high-temperature roasting and acid washing to simultaneously achieve the incorporation of phosphorus atoms and the construction of a hierarchical pore structure. The process route is simple, the raw material cost is relatively low, and it is easy to achieve the large-scale production of phosphorus-doped nanocarbon cage materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 is a transmission electron microscope image of the phosphorus-doped nanocarbon cage material prepared in Preparation Example 1;
[0020] Figure 2 is a Raman spectrum of the phosphorus-doped nanocarbon cage material prepared in Preparation Example 1-4;
[0021] Figure 3 This is the Raman spectrum of the nano-carbon cage material prepared in Comparative Example 1;
[0022] Figure 4 is a rate curve diagram of the negative electrode of the lithium ion capacitor prepared in Example 1;
[0023] Figure 5 is a cycle curve diagram of the negative electrode of the lithium ion capacitor prepared in Example 1;
[0024] Figure 6 is a rate curve diagram of the negative electrode of the lithium ion capacitor prepared in Example 2;
[0025] Figure 7 is a cycle curve diagram of the negative electrode of the lithium ion capacitor prepared in Example 2;
[0026] Figure 8 is a rate curve diagram of the negative electrode of the lithium ion capacitor prepared in Example 3;
[0027] Fig. 9 is a cycle curve diagram of the negative electrode of the lithium ion capacitor prepared in Example 3;
[0028] Fig.10 is a rate curve diagram of the negative electrode of the lithium ion capacitor prepared in Example 4;
[0029] Fig.11 is a cycle curve diagram of the negative electrode of the lithium ion capacitor prepared in Example 4;
[0030] Fig.12 is a rate curve diagram of the negative electrode of the lithium ion capacitor prepared in Comparative Example 1;
[0031] Fig.13 This is a cycle curve diagram of the negative electrode of the lithium ion capacitor prepared in Comparative Example 1. DETAILED DESCRIPTION
[0032] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0033] The first aspect of the present invention provides a phosphorus-doped nanocarbon cage material, wherein the nanocarbon cage material has a microporous structure and a mesoporous structure, and the total specific surface area of the nanocarbon cage material is 300-600m 2 / g, the specific surface area of micropores is 50-130m 2 / g, accounting for 10-25% of the total specific surface area; the average pore size is 10-20nm; the atomic percentage content of carbon on the surface of the nano carbon cage material measured by X-ray photoelectron spectroscopy is 90-97.5%, and the atomic percentage content of phosphorus is 0.01-1%.
[0034] In the present invention, the term "mesopore" is defined as a pore with a pore size in the range of 2-50 nm; and "micropore" is defined as a pore with a pore size less than 2 nm.
[0035] According to some embodiments of the present invention, the total specific surface area of the nanocarbon cage material is 300-600m 2 / g, the specific surface area of micropores is 50-130m 2 / g, accounting for 10-25% of the total specific surface area;
[0036] Preferably, the total specific surface area of the nanocarbon cage material is 350-560 m 2 / g, the specific surface area of micropores is 55-128.5m 2 / g, accounting for 11-24% of the total specific surface area.
[0037] According to some embodiments of the present invention, the average pore diameter of the nanocarbon cage material is 10-20 nm, preferably 12.5-15.5 nm.
[0038] According to some embodiments of the present invention, the pore structure properties of the material are measured by a Quantachrome AS-6B analyzer, and the specific surface area and pore volume of the material are obtained by a Brunauer-Emmett-Taller (BET) method.
[0039] According to some embodiments of the present invention, the atomic percentage content of carbon on the surface of the nano-carbon cage material is 90-97.5%, and the atomic percentage content of phosphorus is 0.01-1% as measured by X-ray photoelectron spectroscopy;
[0040] Preferably, the atomic percentage content of carbon on the surface of the nano-carbon cage material measured by X-ray photoelectron spectroscopy is 90.5-95.5%, and the atomic percentage content of phosphorus is 0.05-0.5%.
[0041] According to some embodiments of the present invention, preferably, the nano-carbon cage material may also contain oxygen element, which may be oxygen element in various forms formed in the phosphorus-doped nano-carbon cage material during the preparation process of the phosphorus-doped nano-carbon cage material; more preferably, the atomic percentage content of oxygen on the surface of the nano-carbon cage material measured by X-ray photoelectron spectroscopy is 3-10%, preferably 5-10%.
[0042] According to some embodiments of the present invention, X-ray photoelectron spectroscopy (XPS) analysis was performed on an ESCALab250 X-ray photoelectron spectrometer equipped with Thermo Avantage V5.926 software from Thermo Scientific, with an excitation source of monochromatic Al Kα X-rays, an energy of 1486.6 eV, a power of 150 W, a narrow scan with a penetration energy of 30 eV, and a basic vacuum of 6.53 × 10 -9 mbar, the electron binding energy was calibrated with the C1s peak (284.6 eV) of elemental carbon, data processing was performed on Thermo Avantage software, and the sensitivity factor method was used for quantitative analysis in the analysis module. Before the material was tested, it was dried in a helium atmosphere at 150°C and 1 standard atmosphere for 3 hours.
[0043] According to some embodiments of the present invention, the phosphorus-doped nanocarbon cage material may contain doping elements that are known to those skilled in the art and can be applied to carbon materials. Preferably, the phosphorus-doped nanocarbon cage material does not contain elements such as nickel, sulfur, nitrogen, boron, fluorine, chlorine, bromine, and iodine.
[0044] According to some embodiments of the present invention, preferably, the nanocarbon cage material is in the shape of a hollow cage, and the hollow cage has a conventional definition in the art, specifically referring to a hollow sphere or quasi-sphere formed by being surrounded by a graphitized carbon layer.
[0045] According to some embodiments of the present invention, the surface morphology of the material is characterized by high-resolution transmission electron microscopy (HRTEM). The model of the high-resolution transmission electron microscope used is JEM-2100 (JEOL Ltd.), and the test conditions of the high-resolution transmission electron microscope are: the acceleration voltage is 200 kV.
[0046] According to some embodiments of the present invention, preferably, in the Raman curve of the nanocarbon cage material, I D / I G The range of is 0.7-1.2, preferably 0.9-1.1. In the Raman curve of the nanocarbon cage material, I D / I G It refers to the intensity ratio of the D peak and the G peak in the Raman curve. The nano carbon cage material of the present invention has obvious D peak and G peak and has a high degree of graphitization.
[0047] According to some embodiments of the present invention, the Raman test adopts a visible laser Raman measurement method, which uses a 532 light source to perform Raman characterization on the functional groups of the material to provide a characteristic spectrum.
[0048] A second aspect of the present invention provides a method for preparing a phosphorus-doped nanocarbon cage material, the method comprising the following steps:
[0049] (1) providing a homogeneous solution containing a nickel salt, an organic acid, a phosphorus-containing compound and a solvent, and then removing the solvent from the homogeneous solution to obtain a precursor material;
[0050] (2) calcining the precursor material at high temperature under the protection of an inert atmosphere to obtain a primary product;
[0051] (3) contacting the primary product with an acid for reaction, and then performing solid-liquid separation.
[0052] According to some embodiments of the present invention, the method for preparing phosphorus-doped nanocarbon cage materials uses nickel salts, organic acids and phosphorus-containing compounds as raw materials to synthesize nickel- and phosphorus-containing precursor materials, which are then calcined under a high-temperature inert atmosphere to obtain a primary product. In this process, nickel atoms act as templates and catalysts, and at the same time, phosphorus-containing compounds can provide sufficient phosphorus atoms. Finally, the metallic nickel in the primary product is removed by pickling to obtain a phosphorus-doped nanocarbon cage material. The material has a microporous structure and a mesoporous structure, and its total specific surface area is 300-600m 2 / g, the specific surface area of micropores is 50-130m 2 / g, accounting for 10-25% of the total specific surface area; the average pore size is 10-20nm; the atomic percentage content of carbon on the surface of the nano carbon cage material measured by X-ray photoelectron spectroscopy is 90-97.5%, and the atomic percentage content of phosphorus is 0.01-1%.
[0053] According to some embodiments of the present invention, in step (1), there is no particular limitation on the method for forming the homogeneous solution, for example, the homogeneous solution may be formed by heating, and more preferably by heating and stirring. There is no particular limitation on the heating temperature and stirring rate, as long as the homogeneous solution can be formed.
[0054] According to some embodiments of the present invention, preferably, in step (1), the nickel salt, the organic acid and the phosphorus-containing compound are dissolved in a solvent to form the homogeneous solution, and then the solvent in the homogeneous solution is removed to obtain a precursor material. There is no particular limitation on the type of the solvent, which is subject to the ability to form a homogeneous solution. Preferably, the solvent is water and / or ethanol, more preferably water; there is no particular limitation on the amount of the solvent, which is also subject to the ability to form a homogeneous solution. The solvent in the solution can be removed by drying, and the drying temperature and process can adopt the existing technology known to those skilled in the art.
[0055] According to some embodiments of the present invention, preferably, in step (1), the nickel salt is selected from at least one of basic nickel carbonate, nickel acetate, nickel chloride and nickel nitrate, preferably basic nickel carbonate.
[0056] According to some embodiments of the present invention, preferably, the organic acid is selected from at least one of citric acid, malic acid, salicylic acid and benzoic acid, preferably citric acid.
[0057] According to some embodiments of the present invention, preferably, the phosphorus-containing compound is selected from dipotassium hydrogen phosphate and / or potassium dihydrogen phosphate, preferably potassium dihydrogen phosphate. Preferably, the phosphorus-containing compound, wherein the presence of potassium atoms is conducive to constructing the hierarchical pore structure in the phosphorus-doped nanocarbon cage material.
[0058] According to some embodiments of the present invention, preferably, in step (1), the molar ratio of the nickel salt, organic acid and phosphorus-containing compound calculated by nickel element is 1:0.5-1:0.1-0.9, for example, it can be 1:0.5:0.1, 1:0.5:0.9, 1:0.7:0.1, 1:0.7:0.7, 1:0.7:0.9, 1:1:0.1, 1:1:0.3, 1:1:0.5, 1:1:0.7, 1:1:0.9 and any value in the range formed by any two of these values. Preferably, the molar ratio of the nickel salt, organic acid and phosphorus-containing compound calculated by nickel element is 1:0.7-1:0.1-0.7. The molar ratio of the nickel salt, organic acid and phosphorus-containing compound calculated by nickel element within the above preferred range is conducive to further promoting the formation of the hollow cage structure of the phosphorus-doped nanocarbon cage material.
[0059] According to some embodiments of the present invention, preferably, in step (2), the inert atmosphere is provided by at least one of nitrogen, argon, neon and helium.
[0060] According to some embodiments of the present invention, preferably, in step (2), the high temperature calcination conditions include: a heating rate of 1-10°C / min, preferably 5-10°C / min; a calcination temperature of 600-1200°C, preferably 650-1000°C; and a calcination time of 2-6h, preferably 2-4h. The high temperature calcination conditions within the above preferred range are conducive to further promoting the formation of the hollow cage structure of the phosphorus-doped nanocarbon cage material and improving its yield.
[0061] According to some embodiments of the present invention, in step (3), the step of contacting the primary product with an acid is preferably: mixing the primary product with an acid, and there is no particular limitation on the mixing method, and the mixing can be carried out by ultrasound or stirring. The acid can be an acid conventionally used in the art, as long as it can form a phosphorus-doped nanocarbon cage material with a hierarchical pore structure with mesopores as the main part and micropores as the auxiliary part.
[0062] According to some embodiments of the present invention, preferably, the acid is an inorganic acid and / or an organic acid, preferably at least one of hydrochloric acid, sulfuric acid, nitric acid and citric acid, more preferably hydrochloric acid. More preferably, the acid is provided in the form of an aqueous solution; further preferably, in the aqueous solution of the acid, the concentration of the acid is 1-12 mol / L.
[0063] According to some embodiments of the present invention, preferably, in step (3), the contact reaction conditions include: temperature of 80-120° C., preferably 90-110° C.; time of 8-12 h, preferably 10-12 h.
[0064] According to some embodiments of the present invention, in step (3), there is no particular limitation on the solid-liquid separation method, and the solid-liquid separation can be performed by any solid-liquid separation method known in the art, for example, solid-liquid separation can be performed by filtration.
[0065] According to some embodiments of the present invention, preferably, in step (3), the solid-liquid separation further includes washing and drying steps. The washing is used to remove the acid remaining on the phosphorus-doped nanocarbon cage material. Therefore, various water washing methods that can wash the phosphorus-doped nanocarbon cage material to neutrality are applicable to the present invention. The drying is used to remove water on the phosphorus-doped nanocarbon cage material. Drying can be carried out by normal pressure drying or reduced pressure drying, and the drying conditions can adopt any feasible existing technology.
[0066] According to some embodiments of the present invention, the phosphorus-doped nanocarbon cage material may contain doping elements that are known to those skilled in the art and can be applied to carbon materials. Preferably, the phosphorus-doped nanocarbon cage material does not contain elements such as nickel, sulfur, nitrogen, boron, fluorine, chlorine, bromine, and iodine.
[0067] The third aspect of the present invention provides a lithium ion capacitor electrode material, which contains an active substance, a conductive agent and a binder. The active substance is the phosphorus-doped nanocarbon cage material described in the first aspect or the phosphorus-doped nanocarbon cage material prepared according to the method described in the second aspect.
[0068] According to some embodiments of the present invention, preferably, the mass ratio of the active material, the conductive agent and the binder is 7-18:1-3:1, for example, it can be 9:0.5:0.5, 8:1:1, 8:1.5:0.5, 7:2:1 and any value in the range formed by any two of these values, preferably 7-10:1-2:1, and more preferably 8:1:1.
[0069] According to some embodiments of the present invention, the content and type of the conductive agent are well known to those skilled in the art. Preferably, the conductive agent is selected from at least one of acetylene black, Ketjen black, graphene and carbon nanotubes, preferably acetylene black.
[0070] According to some embodiments of the present invention, the binder can be any binder known in the art that can be used for lithium ion capacitors, preferably a fluorine-containing resin and / or a polyolefin compound, more preferably, the binder is selected from at least one of polytetrafluoroethylene, polyvinylidene fluoride, sodium carboxymethyl cellulose, polyvinyl alcohol, styrene-butadiene rubber emulsion and acrylonitrile copolymer aqueous dispersion, more preferably polytetrafluoroethylene.
[0071] A fourth aspect of the present invention provides a negative electrode for a lithium ion capacitor, the negative electrode comprising a current collector and an electrode material coated and / or filled on the current collector, the electrode material being the lithium ion capacitor electrode material described in the third aspect.
[0072] According to some embodiments of the present invention, preferably, the current collector is selected from stainless steel mesh and / or copper foil, preferably stainless steel mesh.
[0073] Since the present invention only involves the improvement of the electrode active material, when the phosphorus-doped nanocarbon cage material of the present invention is applied to a lithium ion capacitor, there is no particular restriction on other components and structures of the lithium ion capacitor.
[0074] The fifth aspect of the present invention provides a method for preparing a negative electrode of a lithium ion capacitor, the method comprising coating and / or filling a slurry containing an active material, a conductive agent, a binder and a solvent on a current collector, drying, and rolling or not rolling, wherein the active material is the phosphorus-doped nanocarbon cage material described in the first aspect or the phosphorus-doped nanocarbon cage material prepared according to the method described in the second aspect.
[0075] According to some embodiments of the present invention, the solvent can be any solvent known in the art that can be used to prepare a negative electrode of a lithium ion capacitor. Preferably, the solvent is anhydrous ethanol and / or N-methylpyrrolidone, preferably anhydrous ethanol. The amount of the solvent used is based on the ability to form the desired coating slurry.
[0076] The present invention will be described in detail below through examples.
[0077] The surface morphology of the material was characterized by high-resolution transmission electron microscopy (HRTEM). The model of the high-resolution transmission electron microscope used was JEM-2100 (JEOL Ltd.), and the test conditions of the high-resolution transmission electron microscope were: the acceleration voltage was 200 kV.
[0078] The pore structure properties of the material were detected by the BET test method. Specifically, the Quantachrome AS-6B analyzer was used for the determination. The specific surface area and pore volume of the material were obtained by the Brunauer-Emmett-Taller (BET) method, the mesopore distribution curve was calculated by the Barrett-Joyner-Halenda (BJH) method for the desorption curve, and the micropore size distribution curve was calculated by the Horvath-Kawazoe (HK) method for the isotherm curve.
[0079] The content of each element on the surface of the material was determined by X-ray photoelectron spectroscopy (XPS). The X-ray photoelectron spectroscopy analysis was carried out on an ESCALab250 X-ray photoelectron spectrometer equipped with Thermo Avantage V5.926 software from Thermo Scientific. The excitation source was monochromatic Al Kα X-ray with an energy of 1486.6 eV and a power of 150 W. The penetration energy used for narrow scanning was 30 eV. The basic vacuum during the analysis test was 6.53×10 -9 mbar, the electron binding energy was calibrated with the C1s peak (284.6 eV) of elemental carbon, data processing was performed on Thermo Avantage software, and the sensitivity factor method was used for quantitative analysis in the analysis module. Before the material was tested, it was dried in a helium atmosphere at 150°C and 1 standard atmosphere for 3 hours.
[0080] Raman testing uses visible laser Raman measurement method, using 532 light source to perform Raman characterization on the functional groups of the material and give a characteristic spectrum.
[0081] The electrochemical properties of the material were obtained by testing at different current densities using the CT2 001A Land battery testing system of Wuhan Blue Electric Company.
[0082] Preparation Examples 1-4 are used to illustrate phosphorus-doped nanocarbon cage materials and preparation methods thereof.
[0083] Preparation Example 1
[0084] (1) dissolving basic nickel carbonate, citric acid and potassium dihydrogen phosphate in an appropriate amount of deionized water in a molar ratio of 1:1:0.1, heating and stirring at 95° C. for 4 h, and then placing in an oven to dry to obtain a precursor material;
[0085] (2) Grinding the precursor material into powder, placing it in a tubular calcining furnace, heating it to 650°C at a heating rate of 5°C / min under the protection of nitrogen, calcining it at a constant temperature for 2 hours, and finally cooling it naturally to room temperature to obtain a black primary product;
[0086] (3) Dissolve the initial product in an appropriate amount of deionized water, stir evenly, and then add excess concentrated hydrochloric acid (concentration is 12 mol / L). Then heat to 95°C and heat and stir for 12 hours. After cooling to room temperature, filter and wash with water until neutral. Put it in an oven and dry it overnight to finally obtain phosphorus-doped nanocarbon cage material.
[0087] The transmission electron microscopy image of the phosphorus-doped nanocarbon cage material is shown in Figure 1 As shown, through Figure 1 It can be seen that the material as a whole presents a complete hollow cage-like structure.
[0088] The BET total specific surface area of the material was calculated by isothermal adsorption-desorption curve to be 486.41 m 2 / g, the specific surface area in micropores is 56.08m 2 / g, accounting for 11.53% of the total specific surface area, and the average pore diameter is 12.98nm, indicating that the pore structure of the material is mainly mesoporous structure.
[0089] The atomic ratio of each element on the surface of the material can be calculated based on the peak area in the X-ray photoelectron spectroscopy (XPS), among which C is 94.62%, O is 5.25%, and P is 0.13%.
[0090] The Raman test results of this material are as follows Figure 2 As shown in the figure, it can be seen that the material has obvious D peak and G peak, I D / I G =1.05, indicating that the material has a certain degree of graphitization.
[0091] Preparation Example 2
[0092] A phosphorus-doped nanocarbon cage material was prepared according to the method of Preparation Example 1, except that the molar ratio of basic nickel carbonate, citric acid and potassium dihydrogen phosphate was 1:1:0.3, and the other preparation processes were the same as Preparation Example 1 to obtain a phosphorus-doped nanocarbon cage material.
[0093] Transmission electron microscopy (TEM) test results show that the material is a hollow cage.
[0094] The BET total specific surface area of the material was calculated to be 361.38 m 2 / g, the specific surface area in micropores is 71.38m 2 / g, accounting for 19.75% of the total specific surface area, and the average pore diameter is 15.07nm, indicating that the pore structure of the material is mainly mesoporous structure.
[0095] The atomic ratio of each element on the surface of the material can be calculated based on the peak area in the X-ray photoelectron spectroscopy (XPS), among which C is 93.91%, O is 5.77%, and P is 0.32%.
[0096] The Raman test results of this material are as follows Figure 2 As shown in the figure, it can be seen that the material has obvious D peak and G peak, I D / I G =0.98, compared with Preparation Example 1, the graphitization degree of the material is improved.
[0097] Preparation Example 3
[0098] A phosphorus-doped nanocarbon cage material was prepared according to the method of Preparation Example 1, except that the molar ratio of basic nickel carbonate, citric acid and potassium dihydrogen phosphate was 1:1:0.5. The other preparation processes were the same as Preparation Example 1 to obtain a phosphorus-doped nanocarbon cage material.
[0099] Transmission electron microscopy (TEM) test results show that the material is a hollow cage.
[0100] The BET total specific surface area of the carbon material was calculated to be 401.94 m 2 / g, the specific surface area in micropores is 82.19m 2 / g, accounting for 20.45% of the total specific surface area, and the average pore diameter is 13.91nm, indicating that the pore structure of the material is mainly mesoporous structure.
[0101] The atomic ratio of each element on the surface of the material can be calculated based on the peak area in the X-ray photoelectron spectroscopy (XPS), among which C is 90.58%, O is 9.13%, and P is 0.29%.
[0102] The Raman test results of this material are as follows Figure 2 As shown in the figure, it can be seen that the material has obvious D peak and G peak, I D / I G =1.02, indicating that the material has a certain degree of graphitization.
[0103] Preparation Example 4
[0104] A phosphorus-doped nanocarbon cage material was prepared according to the method of Preparation Example 1, except that the molar ratio of basic nickel carbonate, citric acid and potassium dihydrogen phosphate was 1:1:0.7. The other preparation processes were the same as Preparation Example 1 to obtain a phosphorus-doped nanocarbon cage material.
[0105] Transmission electron microscopy (TEM) test results show that the material is a hollow cage.
[0106] The BET total specific surface area of the carbon material was calculated by isothermal adsorption-desorption curve to be 557.14 m 2 / g, micropore internal surface area is 128.50m 2 / g, accounting for 23.06% of the total specific surface area, and the average pore diameter is 14.48nm, indicating that the pore structure of the material is mainly mesoporous structure.
[0107] The atomic ratio of each element on the surface of the material was calculated based on the peak area of X-ray photoelectron spectroscopy (XPS), wherein C was 92.34%, O was 7.60%, and P was 0.06%.
[0108] The Raman test results of this material are as follows Figure 2 As shown in the figure, it can be seen that the material has obvious D peak and G peak, I D / I G =0.99, indicating that the material has a certain degree of graphitization.
[0109] Comparative Preparation Example 1
[0110] The nanocarbon cage material was prepared according to the method of Preparation Example 1, except that in step (1), basic nickel carbonate and citric acid were dissolved in an appropriate amount of deionized water in a molar ratio of 1:1, heated and stirred at 95°C for 4 hours, and then placed in an oven to dry to obtain a precursor material; the other preparation processes were the same as those in Preparation Example 1, and finally an undoped nanocarbon cage material was obtained.
[0111] Transmission electron microscopy (TEM) test results show that the material is a hollow cage.
[0112] The BET total specific surface area of the material was calculated to be 264.96 m 2 / g, the specific surface area in micropores is 8.28m 2 / g, accounting for 3.13% of the total specific surface area, and the average pore diameter is 15nm, indicating that the material is almost a fully mesoporous structure.
[0113] The atomic ratio of each element on the surface of the material can be calculated based on the peak area in the X-ray photoelectron spectroscopy (XPS), among which C is 88.42%, O is 6.34%, and Ni is 5.24%.
[0114] The Raman test results of this material are as follows Figure 3 As shown in the figure, it can be seen that the material has obvious D peak and G peak, I D / I G =1.00, indicating that the material has a certain degree of graphitization.
[0115] Examples 1-4 are used to illustrate lithium ion capacitor electrode materials, capacitor negative electrodes and preparation methods thereof.
[0116] Example 1
[0117] Preparation of the negative electrode of a lithium ion capacitor: The phosphorus-doped nanocarbon cage material, acetylene black and polytetrafluoroethylene prepared in Preparation Example 1 are mixed in a mass ratio of 8:1:1, an appropriate amount of anhydrous ethanol is dropped into it, and it is fully ground into a uniform slurry, which is then coated on a stainless steel mesh current collector and dried at 80°C under vacuum conditions to obtain a negative electrode of a lithium ion capacitor.
[0118] Example 2
[0119] A negative electrode for a lithium ion capacitor was prepared according to the method of Example 1, except that the active material was the phosphorus-doped nanocarbon cage material prepared in Preparation Example 2, and the other preparation processes were the same as in Example 1 to obtain a negative electrode for a lithium ion capacitor.
[0120] Example 3
[0121] A negative electrode for a lithium ion capacitor was prepared according to the method of Example 1, except that the active material was the phosphorus-doped nanocarbon cage material prepared in Preparation Example 3, and the other preparation processes were the same as in Example 1 to obtain a negative electrode for a lithium ion capacitor.
[0122] Example 4
[0123] A negative electrode for a lithium ion capacitor was prepared according to the method of Example 1, except that the active material was the phosphorus-doped nanocarbon cage material prepared in Preparation Example 4, and the other preparation processes were the same as in Example 1 to obtain a negative electrode for a lithium ion capacitor.
[0124] Comparative Example 1
[0125] A negative electrode for a lithium ion capacitor was prepared according to the method of Example 1, except that the active material was the nano-carbon cage material prepared in Comparative Preparation Example 1, and the other preparation processes were the same as in Example 1 to obtain a negative electrode for a lithium ion capacitor.
[0126] Test Case
[0127] This test example is used to illustrate the electrochemical performance of the negative electrode of a lithium ion capacitor made using the phosphorus-doped nanocarbon cage material provided by the present invention.
[0128] In a glove box filled with high-purity nitrogen (O2 mass fraction < 10 -6 , H2O mass fraction <10 -6 ), the negative electrodes of the lithium ion capacitors of Examples 1-4 were used as working electrodes, the metal lithium sheet was used as the counter electrode, the Celgard 2400 polypropylene film was used as the separator, and the 1 mol / L LiPF6 ethylene carbonate (EC)-diethyl carbonate (DEC) (volume ratio 1:1) solution was used as the electrolyte to assemble into CR 2032 type half-cells A1-A4, and then allowed to stand for 3 hours.
[0129] The electrochemical performance of half-cells A1-A4 was tested using the CT2 001A Land battery testing system of Wuhan Landian Company, with the charge and discharge voltage range being 0-3V.
[0130] The negative electrode of the lithium ion capacitor prepared in Example 1 has a specific capacity of 400 mAh / g at a current density of 100 mA / g. When the current density is increased to 1 A / g, the specific capacity is 125 mAh / g. Figure 4 After 500 cycles at a current density of 1A / g, the capacity retention rate reached 95% and the coulombic efficiency exceeded 99.5%, showing excellent cycle stability. Figure 5 shown.
[0131] The negative electrode of the lithium ion capacitor prepared in Example 2 has a specific capacity of 475 mAh / g at a current density of 100 mA / g. When the current density is increased to 1 A / g, the specific capacity is 280 mAh / g. Figure 6 After 500 cycles at a current density of 1A / g, the capacity retention rate is 85% and the coulombic efficiency exceeds 99.5%, showing excellent cycle stability. Figure 7 shown.
[0132] The negative electrode of the lithium ion capacitor prepared in Example 3 has a specific capacity of 485 mAh / g at a current density of 100 mA / g. When the current density is increased to 1 A / g, the specific capacity is 255 mAh / g. Figure 8 After 500 cycles at a current density of 1A / g, the capacity retention rate is 94% and the coulombic efficiency exceeds 99.5%, showing excellent cycle stability. Fig. 9 shown.
[0133] The negative electrode of the lithium ion capacitor prepared in Example 4 has a specific capacity of 590 mAh / g at a current density of 100 mA / g. When the current density is increased to 1 A / g, the specific capacity is 285 mAh / g. Fig.10 After 500 cycles at a current density of 1A / g, the capacity retention rate is close to 100%, and the coulombic efficiency exceeds 99.5%, showing excellent cycle stability. Fig.11 shown.
[0134] Comparative test example
[0135] A half-cell was assembled according to the method of the test example, except that the negative electrode of the lithium ion capacitor in comparative example 1 was used as the working electrode. The other assembly processes were the same as those in the test example to obtain a CR 2032 half-cell D1. The electrochemical performance of D1 was tested according to the method of the test example.
[0136] The negative electrode of the lithium ion capacitor prepared in Comparative Example 1 has a specific capacity of only 228 mAh / g at a current density of 100 mA / g. When the current density is increased to 1 A / g, the specific capacity is only 70 mAh / g. Fig.12 After 500 cycles at a current density of 1A / g, the capacity retention rate is less than 95% and the coulombic efficiency exceeds 99.5%, as shown in Figure 2. Fig.13 shown.
[0137] It can be seen from the above data that the negative electrode of the lithium ion capacitor prepared by using the phosphorus-doped nano-carbon cage material provided by the present invention exhibits excellent specific capacity, cycle performance and rate performance.
[0138] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A phosphorus-doped nanocarbon cage material, characterized in that: The nano carbon cage material has a microporous structure and a mesoporous structure, and the total specific surface area of the nano carbon cage material is 300-600 m 2 / g, the specific surface area of micropores is 50-130m 2 / g, accounting for 10-25% of the total specific surface area; the average pore size is 10-20nm; the atomic percentage content of carbon on the surface of the nano-carbon cage material measured by X-ray photoelectron spectroscopy is 90-97.5%, and the atomic percentage content of phosphorus is 0.01-1%.
2. The phosphorus-doped nanocarbon cage material according to claim 1, wherein: The total specific surface area of the nano carbon cage material is 350-560m 2 / g, the specific surface area of micropores is 55-128.5m 2 / g, accounting for 11-24% of the total specific surface area; the average pore size is 12.5-15.5nm; the atomic percentage content of carbon on the surface of the nano-carbon cage material measured by X-ray photoelectron spectroscopy is 90.5-95.5%, and the atomic percentage content of phosphorus is 0.05-0.5%.
3. The phosphorus-doped nanocarbon cage material according to claim 1 or 2, wherein: The nano carbon cage material is a hollow cage; and / or, in the Raman curve of the nano carbon cage material, I D / I G The range is 0.7-1.
2.
4. The phosphorus-doped nanocarbon cage material according to claim 3, wherein: In the Raman curve of the nanocarbon cage material, I D / I G The range is 0.9-1.
1.
5. A method for preparing the phosphorus-doped nanocarbon cage material according to any one of claims 1 to 4, characterized in that: The method comprises the following steps: (1) providing a homogeneous solution containing a nickel salt, an organic acid, a phosphorus-containing compound and a solvent, and then removing the solvent from the homogeneous solution to obtain a precursor material; (2) calcining the precursor material at a high temperature under an inert atmosphere to obtain a primary product; (3) contacting the primary product with an acid for reaction, and then performing solid-liquid separation.
6. The method according to claim 5, wherein: In step (1), the nickel salt is selected from at least one of basic nickel carbonate, nickel acetate, nickel chloride and nickel nitrate; and / or, the organic acid is selected from at least one of citric acid, malic acid, salicylic acid and benzoic acid; and / or, the phosphorus-containing compound is selected from dipotassium hydrogen phosphate and / or potassium dihydrogen phosphate; And / or, the solvent is water and / or ethanol.
7. The method according to claim 6, wherein: In step (1), the nickel salt is basic nickel carbonate; And / or, the organic acid is citric acid; And / or, the phosphorus-containing compound is potassium dihydrogen phosphate; And / or, the solvent is water.
8. The method according to any one of claims 5 to 7, wherein: In step (1), the molar ratio of the nickel salt, the organic acid and the phosphorus-containing compound calculated on the basis of nickel element is 1:0.5-1:0.1-0.
9.
9. The method according to claim 8, wherein: In step (1), the molar ratio of the nickel salt, the organic acid and the phosphorus-containing compound calculated on the basis of nickel element is 1:0.7-1:0.1-0.
7.
10. The method according to claim 5, wherein: In step (2), the high temperature calcination conditions include: a heating rate of 1-10°C / min; a calcination temperature of 600-1200°C; and a calcination time of 2-6h.
11. The method according to claim 10, wherein: In step (2), the high temperature calcination conditions include: a heating rate of 5-10°C / min; a calcination temperature of 650-1000°C; and a calcination time of 2-4h.
12. The method according to claim 5, wherein: In step (3), the contact reaction conditions include: temperature of 80-120°C; time of 8-12h; And / or, the acid is an inorganic acid and / or an organic acid.
13. The method according to claim 12, wherein: In step (3), the contact reaction conditions include: temperature of 90-110°C; time of 10-12h; And / or, the acid is at least one of hydrochloric acid, sulfuric acid, nitric acid and citric acid.
14. The method according to claim 13, wherein: The acid is hydrochloric acid.
15. A lithium ion capacitor electrode material, comprising an active material, a conductive agent and a binder, characterized in that: The active material is the phosphorus-doped nanocarbon cage material according to any one of claims 1 to 4.
16. The lithium ion capacitor electrode material according to claim 15, wherein The mass ratio of the active material, the conductive agent and the binder is 7-18:1-3:
1.
17. The lithium ion capacitor electrode material according to claim 16, wherein The mass ratio of the active material, the conductive agent and the binder is 7-10:1-2:
1.
18. A negative electrode for a lithium ion capacitor, comprising a current collector and an electrode material coated and / or filled on the current collector, characterized in that: The electrode material is the lithium ion capacitor electrode material according to any one of claims 15 to 17.
19. The negative electrode for a lithium ion capacitor according to claim 18, wherein: The current collector is selected from stainless steel mesh and / or copper foil.
20. The negative electrode for a lithium ion capacitor according to claim 19, wherein: The current collector is a stainless steel mesh.
21. A method for preparing a negative electrode of a lithium ion capacitor, the method comprising coating and / or filling a slurry containing an active material, a conductive agent, a binder and a solvent on a current collector, drying, and rolling or not rolling, characterized in that: The active material is the phosphorus-doped nanocarbon cage material according to any one of claims 1 to 4.
22. The method according to claim 21, wherein: The conductive agent is selected from at least one of acetylene black, Ketjen black, graphene and carbon nanotubes; and / or, the binder is selected from at least one of polytetrafluoroethylene, polyvinylidene fluoride, sodium carboxymethyl cellulose, polyvinyl alcohol, styrene-butadiene rubber emulsion and acrylonitrile copolymer aqueous dispersion; And / or, the solvent is anhydrous ethanol and / or N-methylpyrrolidone.
23. The method according to claim 22, wherein: The conductive agent is acetylene black; And / or, the binder is polytetrafluoroethylene; And / or, the solvent is anhydrous ethanol.
Citation Information
Patent Citations
Method for mass preparing hollow nano cages in high quality
CN101284663A
Boron containing porous carbon electrode material and preparation thereof
CN101388291A
Nanoscale intercalation materials on carbon powder, process for production, and use thereof
US20110281176A1